PERANAN ORANG TUA DALAM MENINGKATKAN KREATIVITAS BELAJAR ANAK DI RUMAH YANG BERADA PADA RT. 08 RW. 03 KELURAHAN AIR PUTIH KECAMATAN TAMPAN KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the role of parents in improving children's learning creativity at home at RT.08 RW.08 in the village of Air Putih in the beautiful sub-district of Pekanbaru. The population in this study were all parents who were on RT.08 RW.03 Air Putih Sub-District, Tampan Subdistrict, Pekanbaru City, namely parents who have children who are still in primary school aged 6-12, amounting to of 50 people and samples in this study, 20 people were used in other places as a test sample on RT.09 RW.01 kelurahan kelurahan in the beautiful district of pekanbaru city. This type of research uses descriptive research with a quantitative approach. The instruments used in this study were observations and questionnaires with 35 item overviews. The role of parents in improving children's learning creativity in RT.08 RW.03 kelurahan Air Putih, handsome neighborhood of pekanbaru with indicators 1) the role of parents as facilitators, 2) the role of parents as motivators, 3) the role of parents as mentors 4) the role of parents as role model. Alternative answers for each item overview have a category that always gets a score of 4 (four), often a score of 3 (three), sometimes with a score of 2 (two), never given a score of 1 (one). The results of this study are some parents of RT.08 RW.03 in the category that is classified as good. This is demonstrated by the presentation of the data capture, namely: 1) the role of parents as facilitators 66.11% of the respondents who have always mentioned (SL) and Frequent (SR) 2) the role of parents as motivators 69.79 % of respondents who have always mentioned Always (SL) and often (SR). 3) The role of the person as supervisor of 69.24% of the respondents who mentioned Always (SL) and Frequently (SR). 4) the role of parents as a role model for 71% of the respondents stating Always (SL and often (SR).Keywords: Role Of Parents, Learning From Creativity